Application of geological strength index system for slope stability studies of the crocker formation in Kota Kinabalu, Sabah - Lee, Kiun You (2017)
The main objective of this study is to apply Geological Strength Index (GSI) classification system for slope stability study in Crocker Formation of Kota Kinabalu area. Six slopes were selected based on different type of composition and structure as in the GSI chart. The geological mapping and discontinuity survey were conducted to obtain quantitative description of discontinuities as well as rock sampling based on rock unit and grain sizes. GSI ratings were analysed using three GSI approaches which are GSI₁₉₉₇, GSI₂₀₀₇ and GSI₂₀₁₃. The results show that GSI₂₀₀₇ was the most suitable GSI approach to be applied at the Crocker Formation. Parameters of disturbance factor (D), uniaxial compressive strength (UCS) and rock mass properties were obtained through field observation, laboratory work and correlation of Hoek-Brown criterion. Based on the results, it was found that, GSI rating has the greatest influence on rock mass properties followed by UCS and disturbance factor. These parameters were directly proportional to the rock mass properties. Intact rock constant however was inversely proportional to cohesion and tensile strength because of the present of shale and silt material. Numerical analyses of kinematic, finite element, (FEA) and limit equilibrium (LEA) analyses were performed to analyse the slope condition. Kinematic analysis showed that only slope S1 and slope S5 have probability for wedge failure. FEA and LEA results indicated that all slopes have the safety factor value that can be considered as stable, with FEA considered to be more suitable method since it can analyse both elastic and plastiC properties (elasto-plastic), additionally, it also capable of handling more complex failure plane and geometry. The safety factors obtained in FEA considered and computed based on rock mass properties which were neglected by LEA. Besides GSI rating, slope geometry also found to influence the slope condition, therefore, this parameter must be incorporated for slope stability analysis. Finally, the rock cut slope design was proposed with focus on mitigating localised failure and reducing water pressure build up behind the slope face. No obvious correlation can be made between GSI and rock cut slope design because it predominantly controlled by geometry, lithology and stability of individual slope rather than GSI rating.